The Relationship between Nurse Support and Compliance Level of Hemodialysis Therapy in Chronic Kidney Failure Patients in the Dialysis Room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Airy Mahsya Elika R. Adam; Nasrun Pakaya; Indra (Universitas Muhammadiyah Palu, 2026)
Chronic kidney failure is a growing health problem and requires regular hemodialysis therapy. The success of therapy is determined by the patient's compliance, but it is still found that patients do not comply with the therapy schedule and recommendations. This study aims to analyze the relationship between nurse support and the level of compliance with hedialysis therapy in patients with chronic kidney failure in the dialysis room of Prof. Dr. dr. H. Aloei Saboe Hospital, Gorontalo City. The research method uses a quantitative design of correlational analytics through a cross-sectional approach. The independent variable is the nurse's support and the dependent variable is the patient's level of compliance with hemodialysis therapy. The population in this study is all patients with chronic kidney failure who underwent hemodialysis as many as 70 patients with total sampling techniques. Data collection using questionnaires and data analysis using the Chi-Square test. The results of the study obtained a p-value = 0.003 (p<0.05). The conclusion of this study is that there is a relationship between nurse support and the level of patient compliance undergoing hemodialysis in patients with chronic kidney failure in the dialysis room of Prof. Dr. dr. H. Aloei Saboe Hospital, Gorontalo City. It is recommended that nurses improve the quality of support through therapeutic education and communication, as well as that patients be more active in increasing awareness and adherence to therapy.